2009
DOI: 10.1111/j.1365-2893.2009.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diagnosis of liver fibrosis in patients with HIV infection and HCV/HBV co‐infection

Abstract: The measurement of fibrosis stage critically affects the identification of the progression of liver disease, the establishment of a prognosis and therapeutic decision making. Liver biopsy has been the single, most useful method to determine the degree of liver fibrosis (LF), but with recognized limitations, mainly associated with its invasiveness. In recent years, alternative noninvasive methods have been developed, including imaging methods, such as transient elastometry, and assays based on serum biomarkers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…Aside from these laboratory biomarkers, liver fibrosis is evaluated using transient elastography (FibroScan) [42]. Our group reported an excellent diagnostic performance of liver stiffness for fibrosis and cirrhosis in HIV/HCV-coinfected patients [43], which was higher than the diagnostic performance of HA shown here.…”
Section: Discussionmentioning
confidence: 92%
“…Aside from these laboratory biomarkers, liver fibrosis is evaluated using transient elastography (FibroScan) [42]. Our group reported an excellent diagnostic performance of liver stiffness for fibrosis and cirrhosis in HIV/HCV-coinfected patients [43], which was higher than the diagnostic performance of HA shown here.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment efficacy should also be evaluated on the basis of liver fibrosis regression under treatment. Two studies based on repeated liver biopsies have reported regression of extensive fibrosis and even cirrhosis under TDF,75 76 also seen by means of non-invasive markers 75 83 84…”
Section: Hepatitis B: Remaining Challenges In Diagnosis Treatment Anmentioning
confidence: 97%
“…The median number of portal tracts was 16 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The median number of portal tracts was 16 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Liver Biopsymentioning
confidence: 99%